PARTISIPASI POLITIK PEREMPUAN DALAM PILKADA TAHUN 2024 DI GAMPONG GUNONG KLENG KABUPATEN ACEH BARAT - Maifizar, Arfriani; Sayumitra, Andi (Journal of Political Sphere, 2025)
Political participation is a constitutional right guaranteed to all citizens, including women. In regional head elections (Pilkada), women play essential roles not only as voters but also as organizers and campaign participants. This study aims to analyze the forms and influencing factors of womens political participation in the 2024 Pilkada in Gampong Gunong Kleng, Aceh Barat District. Using a qualitative case study approach, data were collected through in-depth interviews, direct observation during the election stages, and documentation from election committees. The findings reveal a significant increase in women's involvement, particularly in roles such as polling officers, witnesses, campaign teams, and active voters. This active participation reflects progress toward a more inclusive and gender-equitable local democracy. The study recommends the implementation of affirmative policies, political education, and the creation of a conducive social environment to enhance women's political engagement.